Improving Understanding of Mathematical Concepts Through Contextual Teaching and Learning (CTL): A Case Study at Junior High School 14 Pematangsiantar - Putri Nazwa; Dian Elita Apriani; Gusti Magdalena Br. Siburian; Romaulika Situmorang; Septri Amelia Simamora; Yarti Melvina Rambe; Yesnita Aprilia; Budi Halomoan Siregar (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2025)
Mathematics learning at the secondary school level plays an important role in fostering a deep understanding of ideas among students. The main purpose of this research is to see how effectively SMP Negeri 14 Pematangsiantar’s students understand mathematical concepts through CTL learning. This research applies a quantitative approach with a true experimental design. The study involved 30 seventh-grade students, divided into an experimental group (15 students of class VII-1) and a control group (15 students of class VII-3). The experimental group received learning with the CTL approach, which incorporated real-life problem-solving activities, discussions, and hands-on contextual exercises related to fractions. Meanwhile, the control group was taught using the expository method. Both groups were given a pre-test and post-test to measure the improvement of learning outcomes. The control group had an average post-test score of 54.00, while the experimental group had a significantly higher score of 90.33 (p < 0.001). Data were analyzed using an independent sample t-test, which confirmed that the difference in post-test scores between the two groups was statistically significant. The findings indicated that the CTL approach significantly improved students' conceptual understanding. The practical implications of this study suggest that integrating contextual learning strategies into mathematics instruction can enhance students’ ability to comprehend abstract concepts, particularly fractions. The findings of this study support the CTL approach as an effective and recommended instructional strategy for improving students' conceptual understanding of fractions. Implementing this approach can contribute to more engaging and meaningful mathematics education at the secondary school level.